Produksi foto sebagai aktivitas komunikasi visual bagi pelaku UMKM Jawa Barat di media digital - Rizca Haqqu (University of Muhammadiyah Malang, 2022)
The media industry will and will always develop from time to time. This makes people accustomed to and adapting to digital technology. One of the sectors that are driven by the impetus of technological development is product marketing by utilizing digital platforms. Photography is an important point that cannot be separated from digital marketing activities. Where the product to be marketed will be designed in such a way, then immortalized in a photo so that the product looks more aesthetic and attracts customers. Community service carried out aims to provide education and assistance to create marketing communication strategies through Photo Production as a Visual Communication Activity for West Java UMKM in digital media to target communities for community service programs for the period 1 of 2022. Members of UMKM fostered by the creative house of BUMN BRI Bandung are one of the UMKM that play a role in the Indonesian economy. Community service activities related to visual communication activities are a form of dedication from Telkom University Communication Science lecturers. Through Photo Production as a provision for community service in the realm of communication science with the Humanities and Media Studies expertise group. The result of this training activity is that the target community can display product photos that are used as digital marketing media.